Stability analysis of cylindrical shells subjected to complex loads - Nhu, Ngo Huong (Vietnam Journal of Mechanics, 2001)
The paper deals with stability analysis of shell on the basis FEM via Castem 2000. The numerical results of stability problems of cylinders subjected to different loads as compress load, pressure, concentrated and combined loads are compared with analytical result and give a good agreement. The influence of changing radius of the cylindrical shell on the unstable forms and the influence of angles of fibers on unstable behaviour of laminated composite shell are considered. Numerical results and corresponding programs by languages Gibian given in the paper to realize software Castem 2000 can be applied in the design and in the stability analysis of the shell with more complex conditions